SEANZA lectures : lectures delivered at the fifth SEANZA Central Banking Course held at Karachi, January 13-March 20, 1964 (Karachi : State Bank of Pakistan, SEANZA Organization, 1964)
This volume consist of lectures delivered at the fifth SEANZA Central Banking Course held at Karachi, January 13-March 20, 1964. The lectures examined the role of commercial banks in developing countries and measures for improving the adequacy of banking facilities.
Includes bibliographical references.
oo 07/03/2019
Loans
Keywords: Economic development; Economic conditions; Finance